2022
DOI: 10.1097/tp.0000000000004203
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Infection With the Omicron SARS-CoV-2 Variant in a Cohort of Kidney and Kidney Pancreas Transplant Recipients: Clinical Features, Risk Factors, and Outcomes

Abstract: Background. Since November 2021, a new variant of concern (VOC), the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) lineage B.1.1.529 (Omicron) has emerged as the dominant coronavirus disease 2019 (COVID-19) infection worldwide. We describe the clinical presentation, risk factors, and outcomes in a cohort of kidney and kidney pancreas transplant recipients with COVID-19 caused by Omicron infection. Methods. We included all kidney and kidney pancreas transplant recipients diagnosed with SARS-CoV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 32 publications
4
17
0
Order By: Relevance
“…However, 11.2% of LTR with breakthrough infections still required hospitalization for COVID-19-associated complications despite fulfilling the recommended vaccination status. These results are in line with mortality (2–10%) and hospitalization rates (3–56%) that were found in SOT [ 25 , 36 , 37 , 38 ] and a small Spanish single-center study that included 30 LTR with a hospitalization and mortality rate of 3.3% [ 25 ].…”
Section: Discussionsupporting
confidence: 86%
“…However, 11.2% of LTR with breakthrough infections still required hospitalization for COVID-19-associated complications despite fulfilling the recommended vaccination status. These results are in line with mortality (2–10%) and hospitalization rates (3–56%) that were found in SOT [ 25 , 36 , 37 , 38 ] and a small Spanish single-center study that included 30 LTR with a hospitalization and mortality rate of 3.3% [ 25 ].…”
Section: Discussionsupporting
confidence: 86%
“…Several studies have examined the outcomes of anti-spike monoclonal antibody therapy in high-risk patients, including specific transplant populations. [6][7][8][9] While much of these data predate the Omicron era, these studies have largely demonstrated overall good outcomes, including low rates of progression to severe infection, hospitalization, and death. Previous anti-spike monoclonal antibody therapies have largely been considered equivalent in effectiveness, assuming the current circulating variant has adequate susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the outcomes of anti‐spike monoclonal antibody therapy in high‐risk patients, including specific transplant populations 6–9 . While much of these data predate the Omicron era, these studies have largely demonstrated overall good outcomes, including low rates of progression to severe infection, hospitalization, and death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we examined unvaccinated KT patients infected with the Omicron BA. imaging, 17% required ICU admission for treatment, while 75% died [15]. A study reported that the mortality rate among 36 KT recipients infected with SARS-CoV-2 was 28% [16].…”
Section: Discussionmentioning
confidence: 99%